The use of Blooket: A Study of Studentâ€™s Perception Enhancing English Vocabulary Mastery - Sartika, Kiki Dwi; Heriyawati, Dwi Fita; Elfianto, Sonny (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
Memorizing vocabulary is hard for certain students; this conventional strategy has so many weaknesses. Therefore, technology has an important role in the scope of teaching and learning EFL. Engaging studentsâ€™ habits with their gadgets, especially in gamification â€œBlooketâ€ is a new way to enhance studentsâ€™ vocabulary mastery. This study stands to examine the use of educational games-based learning to enhance Studentsâ€™ English vocabulary. A qualitative study will be carried out as a study-based design and focus on studentsâ€™ perception of playing the Blooket game.Â  40 students (7,8 and 9 grades of Junior High School students) were involved as a subject of research. A questionnaire was given to students using Google Forms to get the data and analyzed it. The result shows that using Blooket can enhance studentsâ€™ motivation in learning vocabulary because it makes them fun, competitive, and understand the vocabulary (not by memorizing). Blooket also has weakness in speed and accuracy because of Internet connection and the gadgetâ€™s performance. Therefore, this can be used as an alternative to breaking the old way of learning vocabulary